Formation of LQ 45 Stock Portfolio Using Sharpe Ratio, Treynor Ratio and Jensen Alpha Metode Methods - Rachmad Rachmad; Totok Sugiharto (Enrichment : Journal of Management, 2021)
This study aims to determine the performance of the LQ 45 stock portfolio using the method Sharpe Ratio, Treynor Ratioand Jensen Alpha and to find out whether or not there are differences between the three methods. This type of research is descriptive quantitative. The sample selection used a purposive random sampling technique, and a sample of 22 stocks was obtained in the 2017 - 2020 period with secondary data. This study uses an analysis with one of the quantitative methods, namely times series analysis. Testing the hypothesis using the Kruskal Wallis H test and the Mean Rank contained in the SPSS software. The test results with Kruskal Wallis obtained x2 0.137 with a probability of 0.937. It is known that the test probability is > 0.05. The results showed that there was no difference between the tests using the three methods. Thus the hypothesis H0 in this study is accepted. The test results between the three treatments have a difference in the mean rank, indicating that there is no significant difference between each treatment. The Sharpe method has the lowest mean rank difference compared to the other two methods, which means that Sharpe is the most consistent with non-difference.